2019
DOI: 10.1007/s00167-019-05682-1
|View full text |Cite
|
Sign up to set email alerts
|

Biceps tenotomy has earlier pain relief compared to biceps tenodesis: a randomized prospective study

Abstract: Purpose Surgical management for long head of the biceps (LHB) tendinopathy with either biceps tenotomy or tenodesis is a reliable, but debated treatment option. The aim of this prospective, randomized, single-blinded study is to evaluate diferences in pain relief and subjective outcomes between biceps tenotomy versus tenodesis for LHB tendinopathy. Methods Subjects were randomized and blinded to biceps tenotomy versus arthroscopic tenodesis intra-operatively. Outcomes evaluated included subjective patient outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
87
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(91 citation statements)
references
References 34 publications
(67 reference statements)
2
87
1
1
Order By: Relevance
“…French orthopedic surgeons popularized arthroscopic tenotomy of the long head of biceps tendon (LHB) as a treatment option for patients with degenerative rotator cuff tears [6]. A tenotomy of the long head of biceps is found to produce an earlier pain relief compared to tenodesis [7] and minimal residual symptoms [8]. Also biceps surgery in combination with a rotator cuff repair, superior outcome is seen [9].…”
Section: Introductionmentioning
confidence: 99%
“…French orthopedic surgeons popularized arthroscopic tenotomy of the long head of biceps tendon (LHB) as a treatment option for patients with degenerative rotator cuff tears [6]. A tenotomy of the long head of biceps is found to produce an earlier pain relief compared to tenodesis [7] and minimal residual symptoms [8]. Also biceps surgery in combination with a rotator cuff repair, superior outcome is seen [9].…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, arthroscopically guided LHBT tenotomy or tenodesis are commonly practiced in cases where spontaneous rupture does not occur, besides often being part of arthroscopic repair of RC tendons [ 15 , 16 ]. These two surgical options for LHBT pathology have shown similar clinical outcomes [ 2 , 17 ], although tenotomy seems to provide earlier pain relief, despite at higher risk of cosmetic deformity due to prominent bump of the muscle belly (Popeye sign), while tenodesis tends to result in superior functional outcomes [ 18 , 19 , 20 ]. The tenotomy is indicated in painful shoulders with ruptured RC tendons in which conservative treatments (rest, rehabilitation, oral anti-inflammatory drugs, steroid injections) have failed, in patients with irreparable injuries and in those not willing to undergo surgery, since a non-negligible number of patients do not wish to undergo shoulder arthroscopic surgery due to their concern for negative outcomes [ 1 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there are two main methods to treat tenosynovitis of LHB brachii including conventional treatments and surgical interventions. Conservative management of symptomatic LHB brachii tendinopathy is usually considered the first-line treatment, such as rest, non-steroidal anti-inflammatory drugs (NSAIDs), corticosteroid injection, and physical therapy [2,6,7]. NSAIDs are the most commonly prescribed drugs for treatment of tenosynovitis [8], which can significantly reduce the intensity of pain and improve the range of motion.…”
Section: Introductionmentioning
confidence: 99%
“…Surgical treatments include long head biceps tenotomy and tenodesis, which are the most common surgical procedures on the treatment of tenosynovitis in clinic [7]. However, studies have reported that surgery also has many limitations, including pain recurrence after operation and varying degrees of joint deformities [6,12,13]. In addition, due to patient's fear of surgery, many patients with tenosynovitis of LHB brachii will not select surgery as their first treatment choice.…”
Section: Introductionmentioning
confidence: 99%